(3GdfcJ GdXQGa Ydi GdCWQGas - (3CMeO Hf Ydj Hf MLQ GdTGaYjs; (3GdMGaX GdeRj , jhSa Hf YHO GdQMef Hf jhSa LeGd GdOjf GdRcj CHh eMeO GdbVGYj GdcdHj, LeGd GdOjf CHh GdMLGL GdMGaX GdeRj,J (B742 (3g` s ((3eMeO YeQ Hf YHO GdYRjR Hf agO s)
(3ChdgG (B:s
(3CeG HYO aEf ef GdcJH GdLdjdI GdeUfaI ai Ydhe GdMOjK cJGH JMaI GdCTQGa HeYQaI GdCWQGa JCdja CHh MLGL jhSa GHf GdRci YHO GdQMef Hf jhSa GdeRi s
(3BNQgG (B:s
(3BNQ eG LeYJg ef MhGTi GdCWQGa s
(3GdfSNI HgG MhGTs
(3GfXQ EjVGM Gdecfhf L(B1 (3U` (B241s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdMOjK h GdeUWdMs